The acetoin assimilation pathway of Pseudomonas putida KT2440 is regulated by overlapping global regulatory elements that respond to nutritional cues. (12th December 2022) - Moreno, Renata; Yuste, Luis; Rojo, Fernando
Abstract: Many microorganisms produce and excrete acetoin (3‐hydroxy‐2‐butanone) when growing in environments that contain glucose or other fermentable carbon sources. This excreted compound can then be assimilated by other bacterial species such as pseudomonads. This work shows that acetoin is not a preferred carbon source of Pseudomonas putida, and that the induction of genes required for its assimilation is down‐modulated by different, independent, global regulatory systems when succinate, glucose or components of the LB medium are also present. The expression of the acetoin degradation genes was found to rely on the RpoN alternative sigma factor and to be modulated by the Crc/Hfq, Cyo and PTS Ntr regulatory elements, with the impact of the latter three varying according to the carbon source present in addition to acetoin. Pyruvate, a poor carbon source for P. putida, did not repress acetoin assimilation. Indeed, the presence of acetoin significantly improved growth on pyruvate, revealing these compounds to have a synergistic effect. This would provide a clear competitive advantage to P. putida when growing in environments in which all the preferred carbon sources have been depleted and pyruvate and acetoin remain as leftovers from the fermentation of sugars by other microorganisms.